2021
DOI: 10.3390/cells10081965
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles-Induced Modifications in Cell Wall Composition in Barley Roots

Abstract: The increased use of nanoparticles (NP) in different industries inevitably results in their release into the environment. In such conditions, plants come into direct contact with NP. Knowledge about the uptake of NP by plants and their effect on different developmental processes is still insufficient. Our studies concerned analyses of the changes in the chemical components of the cell walls of Hordeum vulgare L. roots that were grown in the presence of gold nanoparticles (AuNP). The analyses were performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 150 publications
0
9
0
Order By: Relevance
“…In addition to changes in cell wall thickness and cell wall components and the use of monoclonal antibodies against pectic and arabinogalactan protein epitopes, researchers found that NPs can induce changes in the cell wall composition of barley roots ( Milewska-hendel et al., 2021 ). Methylesterified homogalacturonan (a major pectin that occurs in the primary cell wall) was observed in rhizodermal walls of the differentiation zone in AuNP-treated barley roots but was not detected in control roots ( Milewska-hendel et al., 2021 ). This suggests that cell wall components can be modified by NPs, potentially affecting the efficiency with which they cross the cell wall.…”
Section: From the Outside To The Inside Of A Cell: How Do Nps Travel ...mentioning
confidence: 99%
“…In addition to changes in cell wall thickness and cell wall components and the use of monoclonal antibodies against pectic and arabinogalactan protein epitopes, researchers found that NPs can induce changes in the cell wall composition of barley roots ( Milewska-hendel et al., 2021 ). Methylesterified homogalacturonan (a major pectin that occurs in the primary cell wall) was observed in rhizodermal walls of the differentiation zone in AuNP-treated barley roots but was not detected in control roots ( Milewska-hendel et al., 2021 ). This suggests that cell wall components can be modified by NPs, potentially affecting the efficiency with which they cross the cell wall.…”
Section: From the Outside To The Inside Of A Cell: How Do Nps Travel ...mentioning
confidence: 99%
“…Gold NPs were only collected in the shoots of Oryza sativa when used with Cucurbita pepo, Raphanus raphanistrum, and other plant species. Positively charged gold nanoparticles tend to be quickly absorbed by plant roots [106]. The entry of NPs into the cell is facilitated by capillary action and osmotic pressure [95].…”
Section: Mechanism Of Translocation and Accumulation Of Nps In Plantsmentioning
confidence: 99%
“…The interactions between NPs and the cell wall may be more complex than previously thought. It has been well documented that nanomaterials could affect the pore size (Houston et al, 2016), thickness (Chen et al, 2021) or even composition of the cell wall (Milewska-Hendel et al, 2021). In general, the larger the particle size of NPs, the more difficult it is for plants to absorb and translocate NPs.…”
Section: The Properties Of Npsmentioning
confidence: 99%